2008
DOI: 10.1186/1471-2474-9-96
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms of the upper extremities and the neck: A cross-sectional study on prevalence and symptom-predicting factors at visual display terminal (VDT) workstations

Abstract: Background: The aim of this study was to determine the prevalence and the predictors of musculoskeletal symptoms in the upper extremities and neck at visual display terminal (VDT) workstations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
73
0
13

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 31 publications
12
73
0
13
Order By: Relevance
“…Workers might need to finish their work deadline and facing with heavy job demands. Our finding is in consistent with study conducted Sweden [9], [27], Brazil [28], Germany [4], Finland [11], Australia [29] and US [30].…”
Section: Discussionsupporting
confidence: 93%
“…Workers might need to finish their work deadline and facing with heavy job demands. Our finding is in consistent with study conducted Sweden [9], [27], Brazil [28], Germany [4], Finland [11], Australia [29] and US [30].…”
Section: Discussionsupporting
confidence: 93%
“…This factor is more frequently investigated as a factor predisposing to MSDs of upper and lower back. A large research, performed by German scientists, also found BMI to be irrelevant with respect to neck complaints in the population of employees working with computers [25]. Not only did our study show associations between indivi dual factors and MSDs of the neck area, but also their associations with work related factors.…”
Section: Discussionsupporting
confidence: 47%
“…One could assume that the respondents of this particular age group had the largest experience of work with computers, which is exactly what our study has confirmed -the respondents with the largest experience of work with a computer had higher probability of the neck complaints. However, other researchers that had studied the relationship between this aspect and the complaints, did not establish any significant associations [9,25]. Many cross sectional [7,9,25] as well as follow up epide miologic [24,26,27] studies acknowledge the relationship between the gender and MSDs of neck.…”
Section: Neck Msd Of Computer Workers O R I G I N a L P A P E R S Ijomentioning
confidence: 99%
See 1 more Smart Citation
“…WMSDs in the neck (WMSDs-N) are the most common work-related upper extremity disorders (WRUEDs), and a large range of individual, physical and psychosocial risk factors are associated with the development of WMSDs-N. Individual factors include age, gender, education level, smoking habits and so on; work-related physical factors include awkward posture during work, bending, static sedentary posture and task demands; work-related psychosocial factors include overtime and time spent working to meet deadlines [5][6][7] . In addition, several studies have shown that ergonomic factors (e.g., work station design) were possibly linked to WRUEDs 8) .…”
mentioning
confidence: 99%